Religion og klasse i et senmoderne perspektiv - Reintoft Christensen, Henrik (Religionsvidenskabeligt tidsskrift, 2023)
ENGLISH ABSTRACT: The concept of class focuses historically on the economic exploitation of labor and on the conflict that arises between the exploited and exploiters. The German sociologists Hartmut Rosa and Andreas Reckwitz contribute in different ways to a new conceptualization of class society. In the culturalized class society the measure of the quality of life is the capacity of the individual to achieve self-realization as a unique and authentic individual. In this society of singularities culture plays a crucial role for the ability to establish meaning and motivation which potentially give religion, religious symbols, and religious narratives an important role in the realization of an authentic and unique life course. The article presents Rosa’s and Reckwitz’ theories and discusses the possible role of religion. Furthermore, it identifies the differences between the classical and the new class society and critically discusses the capacity of contemporary sociology of religion to grasp the consequences of their theories.